Pengembangan E-Big Book pada Pembelajaran Membaca Pemahaman Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - Flawery, Adillah Ayu; Desyandri, Desyandri (Asian Journal of Early Childhood and Elementary Education, 2025)
This study aims to develop e-big book learning media based on problem-based learning model in improving reading comprehension skills of grade IV elementary school students. The research method used is research and development (R&D) with the ADDIE development model which consists of five stages: analysis, design, development, implementation, and evaluation. The e-big book media was developed using Canva and Book Creator applications, and validated by material experts, media experts, and linguists. The validation results showed that this media was very valid with an average percentage of 91%. The practicality test was conducted with teacher and learner response questionnaires, which showed that this media was very practical to use in learning. Furthermore, the effectiveness test based on the pre-test and post-test results showed a significant increase in students' reading comprehension. Thus, e-big book based on problem-based learning proved to be valid, practical, and effective in improving the reading comprehension skills of grade IV elementary school students.